UFIDA (B) - Chen, E., (SAGE knowledge. Cases., 2016)
This case highlights the leadership, cultural and organizational structure dimensions of UFIDA. The case begins with Founder/Chairman Wang Wenjing's rags-to-riches story. Then UFIDA's senior and middle management of different backgrounds talk about their leader, Chairman Wang Wenjing. They voice their opinions on Wang Wenjing's leadership style, UFIDA's corporate culture and vision.